Sistem Monitoring dan Penyiraman Otomatis Pada Bibit Sawit Berbasis Android - Fajar, Muhammad Holid; Waluyo, Anita Fira (Infotek: Jurnal Informatika dan Teknologi, 2024)
The quality of oil palm fruits is very important, and effective seedling care is one of the techniques to produce quality oil palm seedlings. However, seedling care is often constrained by watering, because seedling owners cannot control oil palm seedlings at all times. The purpose of this project is to create a tool and mobile application used to control soil moisture and automatic watering based on android In this study, sensor testing and interviews were used as data collection methods. To determine soil moisture, this system uses a soil moisture sensor. Then the NodeMCU ESP8266 microcontroller will process the data obtained from the sensor, after which the data will be stored in real time in the Firebase realtime database. Android applications made with the Java programming language can be used for monitoring. This system can facilitate the owners of oil palm seedlings in controlling and watering the seedlings, even though they are traveling, the owner of the seedlings can control the oil palm seedlings using the Android application, so that with regular seedling care it will produce quality oil palm